USE OF SOCIAL MEDIA IN THE TOURISM INDUSTRY - Khan, Mohammad Danish; Pavlíček, Antonín, 1977-; Böhmová, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
Social media is a successful platform to connect people of all ages and corners of the world. People connect, share, read, and communicate their ideas, likes, dislikes, emotion, and so many things on social media. On the business level companies, organizations, political parties use social media to communicate, advertising, convincing and exploring products and services to their respondents. Social media become as popular in all walks of life as important networks for information. In some of the fields it is considered the big factors like the tourism industry, advertisement; hospitality and rest of the fields are not apart from it. In many research and studies conducted by the companies, social media have an impact on buying decision, purchasing the product and services, and the reviews of brands before buying, during buying, and after buying process. In support of consumer behavior blogs are also big impact
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses